2010
DOI: 10.1007/s11748-009-0557-3
|View full text |Cite
|
Sign up to set email alerts
|

Atypical carcinoid of thymus associated with multiple endocrine neoplasia syndrome type 1

Abstract: Thymic carcinoid associated with multiple endocrine neoplasia syndrome type 1 (MEN-1) is a rare tumor. We report a case of MEN-1-related thymic carcinoid. The patient reported herein had already been diagnosed with MEN-1 and was found to have a mediastinal mass. She underwent thymectomy with partial resection of the left innominate vein and lung. Histological examination revealed atypical carcinoid with infi ltration. MEN-1 gene mutation was detected by employing the direct nucleotide sequencing method. Postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…While the reasons for this difference are unclear, ethnicity could be one explanation. Several additional case reports exist on Japanese female MEN1 patients with Th‐NET who have not been registered in our database . Similarly, there have been some case reports from Asian and Western countries on female MEN1 patients with Th‐NET, indicating that there may be more female Th‐NET patients than previously considered.…”
Section: Discussionmentioning
confidence: 92%
“…While the reasons for this difference are unclear, ethnicity could be one explanation. Several additional case reports exist on Japanese female MEN1 patients with Th‐NET who have not been registered in our database . Similarly, there have been some case reports from Asian and Western countries on female MEN1 patients with Th‐NET, indicating that there may be more female Th‐NET patients than previously considered.…”
Section: Discussionmentioning
confidence: 92%
“…Thymus carcinoid MEN1-related thymic carcinoid is often insidious with a poor prognosis. In a French MEN1 group, thymic tumors were exclusively found in males [30], whereas in Japan, 37% of MEN1 thymus carcinoid was found in females [31,94].…”
Section: Carcinoid Tumorsmentioning
confidence: 94%
“…However, a Japanese series showed that 36% of MEN-1 patients with thymic carcinoids were female: of the 10 patients only one was a smoker. In addition, there are several case reports from Asia on female MEN-1 patients with thymic carcinoids [32,33] . However, in a series from the MD Anderson hospital in Houston in 2016, there was a similar male/female ratio of 2: 1 in both ethnic groups, suggesting that ethnic differences might not be significant [34] .…”
Section: Differences Between Asians and Caucasiansmentioning
confidence: 99%